2007
DOI: 10.1242/dev.011262
|View full text |Cite
|
Sign up to set email alerts
|

Specification of hypothalamic neurons by dual regulation of the homeodomain protein Orthopedia

Abstract: In the developing hypothalamus, a variety of neurons are generated adjacent to each other in a highly coordinated, but poorly understood process. A critical question that remains unanswered is how coordinated development of multiple neuronal types is achieved in this relatively narrow anatomical region. We focus on dopaminergic (DA) and oxytocinergic (OT) neurons as a paradigm for development of two prominent hypothalamic cell types. We report that the development of DA and OT-like neurons in the zebrafish is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(156 citation statements)
references
References 45 publications
1
146
3
1
Order By: Relevance
“…Forward and reverse genetic approaches in zebrafish have uncovered novel factors involved in vertebrate mesodiencephalic development. Embryos with loss of function in genes encoding the zinc finger-containing protein Fezf2/Fezl and the homeodomain-containing protein Otp display deficits in diencephalic DA neurons (Levkowitz et al, 2003;Del Giacco et al, 2006;Blechman et al, 2007;Ryu et al, 2007). We showed that the transcription factor Fezf2/Fezl, and the G protein-coupled receptor PAC1 act upstream of Otp to trigger specific differentiation programs that promote DA fates (Blechman et al, 2007).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Forward and reverse genetic approaches in zebrafish have uncovered novel factors involved in vertebrate mesodiencephalic development. Embryos with loss of function in genes encoding the zinc finger-containing protein Fezf2/Fezl and the homeodomain-containing protein Otp display deficits in diencephalic DA neurons (Levkowitz et al, 2003;Del Giacco et al, 2006;Blechman et al, 2007;Ryu et al, 2007). We showed that the transcription factor Fezf2/Fezl, and the G protein-coupled receptor PAC1 act upstream of Otp to trigger specific differentiation programs that promote DA fates (Blechman et al, 2007).…”
Section: Introductionmentioning
confidence: 68%
“…Sim1, studied herein in the context of DA differentiation, is crucial for terminal differentiation of the neuroendocrine lineage (Michaud et al, 1998). Otp, which is another critical determinant of neuroendocrine differentiation (Acampora et al, 1999;Wang and Lufkin, 2000), has recently been found to play an important role in specifying diencephalic DA neurons (Del Giacco et al, 2006;Blechman et al, 2007;Ryu et al, 2007). Thus, both Otp and Sim1 are part of an evolutionarily conserved genetic network controlling the specification of the neuroendocrine lineage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To identify the molecular events underlying the synthesis of oxytocin, we screened the zebrafish model organism database (ZFIN) (Bradford et al, 2011) for transcriptional regulators expressed in the neurosecretory preoptic area (NPO), which includes neurons expressing the zebrafish homolog of oxytocin, termed oxytocin-like (Oxtl) (Blechman et al, 2007). One such candidate was the gene encoding the zebrafish ortholog of the transcriptional coactivator PGC-1␣ (LeMoine et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In situ hybridization and immunostaining were performed as previously described (Blechman et al, 2007;. Total RNA was prepared from fish larvae using the TRI-REAGENT (Molecular Research Center) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%